Analysis Of Daily Physical Activities On Mentrual Disorders In Students Of The Faculty Of Public Health Halu Oleo University - Hardi; Juraiti, Warti; Harleni; Abbas, Akhmadi; Harjunita, Ria; Tosepu, Ramadhan; Efendy, Devi Savitri; Susanty, Sri (Universitas Mandala Waluya, 2024)
Menstrual disorders mainly occur in late adolescence. This condition occurs in the first two years after menarche. This study aims to analyze daily physical activity and irregular menstrual disorders in students at the Faculty of Public Health, Halu Oleo University. The research design used was a cross-sectional study. The subjects in this research were students from the Faculty of Public Health, Halu Oleo University, class 2020-2022, who met the inclusion and exclusion criteria of 90 respondents. The results of this study showed that 50% of respondents were in the moderate physical activity category, and the majority (62.2%) experienced irregular menstrual disorders. The results of statistical analysis of physical activity on menstrual disorders obtained p-value=0.000 (p<0.05). This research concludes a significant relationship between physical activity and menstrual disorders in students at the Faculty of Public Health, Halu Oleo University. Female students need to control their physical activity to overcome menstrual disorders.